In Situ Hybridization of RD114-Virus RNA with Human Metaphase Chromosomes - Price, Peter M. (1973)
In situ hybridization was used to detect regions of human metaphase chromosomes exhibiting complementarity with radioactively-labeled RNA isolated from RD114-virus. The region of homology, as identified by autoradiography, was confined to one D-group chromosome.